2021
DOI: 10.1038/s41598-021-95481-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the association between vitamin D and ovarian reserve

Abstract: It is hypothesized that vitamin D deficiency could be related to ovarian reserve. This systematic review and meta-analysis was undertaken to analyze the possible association between vitamin D and ovarian reserve among adolescent and adult women. All eligible studies identified through the ISI Web of Science, PubMed, and Scopus were included up to May 2021. A random-effects meta-analysis model was implemented and a weighted mean difference (WMD) and 95% confidence interval (CI) were calculated. A total of 38 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…This review had some limitations. First, the evaluated articles differed regarding the commercial kits they used for measuring serum vitamin levels (42). Second, many factors, including seasonal differences, sunscreen creams, geographic region, race, skin color, lifestyle, and nutrition, could influence the amount, synthesis, and availabilities of vitamins, and the reviewed studies did not consider all these influencing factors when assessing the relationship between serum level of fat-soluble proteins and POI (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…This review had some limitations. First, the evaluated articles differed regarding the commercial kits they used for measuring serum vitamin levels (42). Second, many factors, including seasonal differences, sunscreen creams, geographic region, race, skin color, lifestyle, and nutrition, could influence the amount, synthesis, and availabilities of vitamins, and the reviewed studies did not consider all these influencing factors when assessing the relationship between serum level of fat-soluble proteins and POI (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is noteworthy that some recent studies, including meta-analyses, have reported promising results showing that vitamin D supplementation led to improvement in ovarian reserve metrics in a subgroup of normal or diminished ovarian reserves. There were three recent meta-analyses published between 2020 and 2022, two of which provided evidence that vitamin D supplements lead to improved ovarian reserve levels in a subgroup of non-PCOS women with normal ovulation or diminished ovarian reserves [ 42 , 43 ], and one found that lower AFC was associated with vitamin D insufficiency/deficiency in a subgroup analysis of Asians [ 44 ]. Moridi et al highlighted that 18 cross-sectional studies had discrepant findings regarding an association between serum vitamin D and AMH levels, which is likely due to heterogeneity in study subjects and the complex nonlinear relationship between vitamin D and AMH in the systematic review.…”
Section: The Association Of Vitamin D and Ovarian Reserve Markersmentioning
confidence: 99%
“…A recent meta-analysis revealed that vitamin D status influences the ovarian reserve: antral follicle count was significantly lower among Asians, and luteinizing Diagnostics 2023, 13, 3024 2 of 12 hormone (LH) levels were higher in non-Asians with inadequate vitamin D levels. Furthermore, a negative correlation was found between vitamin D and the LH/FSH ratio in women with normal body mass index [17]. In addition, the active form of VD (1,25dihydroxy-vitamin D) stimulates aromatase activity [18].…”
Section: Introductionmentioning
confidence: 98%